Current state and the support system of athlete wellbeing in Japan: The perspectives of the university student-athletes - Noguchi, Yoriko; Kuribayashi, Chisato; Kinugasa, Taisuke (Frontiers in Psychology, 2022)
The optimization of athletes’ wellbeing has been increasingly considered essential both in the academic and practical fields of high-performance sports. Various organizations, such as the International Olympic Committee, have highlighted its importance, particularly mental health. Moreover, the increased attention to athlete wellbeing in sport policy debates at the national level has led to the development and implementation of a support system for athletes’ mental wellbeing in some countries. Nevertheless, the literature is limited to understanding the case of Japan. Interestingly, only 0.8% of the literature is available on “athlete” and “wellbeing” in Japanese compared to English journals up to 2019. Therefore, the purpose of this study was to identify (a) the current state of wellbeing of Japanese university student-athletes, (b) the level of knowledge about athlete wellbeing, and (c) the athletes’ perception of the availability of wellbeing support in the national sports federations, (d) the athlete experience of support services, and develop the types of national support athletes expect and need from the government and national sports federations in the future. As a pilot study, a total of 100 Japanese university student-athletes (43 male, 57 female) from 17 Olympic and seven Paralympic sports completed an online survey. Consequently, the state of their wellbeing was self-perceived as good in all dimensions (i.e., physical, mental, educational, organizational, social, and financial). Moreover, the results showed low recognition of the term “athlete wellbeing” and a lack of knowledge of the availability and accessibility of appropriate support services. The results also showed that Japanese university student-athletes rarely seek help from experts, while 45% indicated “no one” to talk to. Interestingly, however, most athletes considered each dimension of wellbeing important in relation to their performance development. Based on the results, it is necessary to develop an education program, guidelines, and detection systems and improve information accessibility. Given that this pilot study’s validity, reliability, and feasibility were verified, further studies should focus more on the wellbeing of Japanese elite athletes in high-performance sports (i.e., Olympic and Paralympic athletes).